Conditionality in Fund-Supported Programs-Purposes, Modalities, and Options for Reform. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper takes a fresh look at the purpose and modalities of conditionality for the use of the Fund's resources. It is part of a broader review of Fund lending facilities that includes access levels, charges and maturities, the analytical basis for Fund lending, and facilities for low income countries. It aims to explore options for more flexible approaches that would be responsive to the changing needs and circumstances of the Fund's members while providing adequate safeguards for Fund resources. While these options have been developed with General Resources Account (GRA) facilities in mind as a complement to the companion paper on the analytical framework, they could apply, as appropriate, to facilities and instruments used by low income members.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Greece